2020
DOI: 10.1177/1073858420937657
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and White Matter Networks

Abstract: The development and persistence of laterality is a key feature of human motor behavior, with the asymmetry of hand use being the most prominent. The idea that asymmetrical functions of the hands reflect asymmetries in terms of structural and functional brain organization has been tested many times. However, despite advances in laterality research and increased understanding of this population-level bias, the neural basis of handedness remains elusive. Recent developments in diffusion magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 169 publications
3
23
0
Order By: Relevance
“…It should be noted that all previous studies that investigated the volume of the sub-regions were based on the midsagittal surface of the CC (Budisavljevic et al, 2020). This makes our tractography results based on CSD more reliable compared to the previous studies.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…It should be noted that all previous studies that investigated the volume of the sub-regions were based on the midsagittal surface of the CC (Budisavljevic et al, 2020). This makes our tractography results based on CSD more reliable compared to the previous studies.…”
Section: Discussionmentioning
confidence: 76%
“…Besides grey matter asymmetries, the interhemispheric interaction, which is mainly conveyed through the corpus callosum (CC), has been suggested to have an association with handedness (Budisavljevic, Castiello, & Begliomini, 2020;. At the functional level, this interaction is explained by two models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies were identified from the reference list of the selected empirical articles and previous review articles (Beaton, 1997;Budisavljevic et al, 2020;Driesen & Raz, 1995) and by contacting authors who recently had published corpus callosum data on handedness.…”
Section: Study Identificationmentioning
confidence: 99%
“…Handedness, arguably the most salient functional asymmetry with almost 9 out of 10 individuals being right-handed (Papadatou-Pastou et al, 2020), has also been frequently related to differences in corpus callosum structure and function (for review see, Beaton, 1997;Budisavljevic, Castiello, & Begliomini, 2020). The origin for this line of research can be found in a series of seminal publications by Sandra Witelson (Witelson, 1985(Witelson, , 1989Witelson & Goldsmith, 1991).…”
Section: Introductionmentioning
confidence: 99%